Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen pada PT. Nasmoco Bengawan Motor dengan Metode ServQual - Putra, Ervin Yulianto Kusuma; , Indah Pratiwi, ST.,MT (2017)
PT. Nasmoco Bengawan Motor as a company engaged in the automotive field it is so important to raise profitability by maintaining the quality. A dynamic condition which affects the output results, services, labor, environmental and process to exceed expectations and with kenyatan are qualities that need to be given to make the company better than ever, the quality improvement into things that must be emphasized because with the quality itself will have a positive impact on the company. Consumer satisfaction is an example of a company introspective to understand the conditions in which the consumer has to be considered in the delivery of a sense of satisfaction. By using the service quality (Gap analysis) finds that there are five dimensions that where there is a gap / gap of reality and expectations are perceived by consumers that dimension is -0.558 (reliability), -0.533 (guarantee), -0.510 (responsiveness), -0.497 (physical evidence), and the last -0.496 (empathy). To find out more about whether the factors that affect service or customer satisfaction then do further testing is using SPSS 16:00 known physical evidence of regression equation (0.644) with significantly 0,00 (physical evidence of a significant effect on satisfaction), reliability (0.445) with a significance of 0.001 (significant effect on the reliability of consumer satisfaction), responsiveness (-0.239) with a significance of 0.121 (responsiveness has no effect on customer satisfaction), assurance (0.445) with a significance of 0.004 (guarantee very significant influence on consumer satisfaction) , and empathy (-0.058) with a significance of 0.060 (empathy affects customer satisfaction. From the regression equation together known value of -1.779 satisfaction, if the first physical evidence that satisfaction will increase -1.135, if the reliability increases first then satisfaction will increase -1.334, if responsiveness increases first then satisfaction will increase -2.018, if the guarantee increases first then increasing satisfaction -1.325, empathy increases first then increased satisfaction -1.721. If the variable service coupled together satisfaction scores will be changed to -0.417